Evaluation of the efficacy of mitochondrial fission inhibitor (Mdivi-1) using non-alcoholic steatohepatitis (NASH) liver organoids - Elbadawy, Mohamed; Tanabe, Kiwamu; Yamamoto, Haru; Ishihara, Yusuke; Mochizuki, Maria; Abugomaa, Amira; Yamawaki, Hideyuki; Kaneda, Masahiro; Usui, Tatsuya; Sasaki, Kazuaki (Frontiers in Pharmacology, 2023)
Non-alcoholic steatohepatitis (NASH) is known to progress to cirrhosis and hepatocellular carcinoma in some patients. Although NASH is associated with abnormal mitochondrial function related to lipid metabolism, mechanisms for the development and effective treatments are still unclear. Therefore, new approaches to elucidate the pathophysiology are needed. In the previous study, we generated liver organoids from different stages of NASH model mice that could recapitulate the part of NASH pathology. In the present study, we investigated the relationship between mitochondrial function and NASH disease by comparing NASH liver organoids (NLO) and control liver organoids (CLO). Compared with CLO, mitochondrial and organoid morphology was abnormal in NLO, with increased expression of mitochondrial mitogen protein, DRP1, and mitochondria-derived reactive oxygen species (ROS) production. Treatment of NLO with a DPR1 inhibitor, Mdivi-1 resulted in the improvement of morphology and the decreased expression of fibrosis-related markers, Col1a1 and Acta2. In addition, treatment of NASH model mice with Mdivi-1 showed a decrease in fatty liver. Mdivi-1 treatment also prevented fibrosis and ROS production in the liver. These results indicate that NLO undergoes enhanced metabolism and abnormal mitochondrial morphology compared with CLO. It was also suggested that Mdivi-1 may be useful as a therapeutic agent to ameliorate NASH pathology.